Cerebral Malaria from a Plasmodium falciparum and Plasmodium malariae Co-Infection: A Case Report on a Diagnostic Challenge - Vera Akmilia; Anak Agung Ayu Yuli Gayatri; Anak Agung Wiradewi Lestari (Archives of The Medicine and Case Reports, 2025)
Severe malaria, primarily caused by Plasmodium falciparum, is a life-threatening medical emergency. Its diagnosis can be significantly complicated by mixed-species infections, where the presence of a less virulent Plasmodium species may mask the true etiological agent of the severe disease, leading to potential delays in appropriate therapy. This report details a case of cerebral malaria where such a diagnostic challenge occurred. An 18-year-old male with a recent travel history to a malaria-endemic area in Indonesia presented with a one-day history of decreased consciousness (Glasgow Coma Scale score of 9) following a week-long febrile illness. The clinical presentation met the World Health Organization's criteria for severe malaria, specifically cerebral malaria. Initial microscopic examination of a peripheral blood smear exclusively identified Plasmodium malariae. However, a concurrently performed rapid diagnostic test (RDT) was positive for both the pan-malarial antigen and the P. falciparum-specific histidine-rich protein 2 (HRP-2) antigen. This critical discordance prompted treatment for severe falciparum malaria with intravenous artesunate and triggered an expert re-evaluation of the blood smears. Subsequent analysis confirmed a co-infection with both P. falciparum and P. malariae. The patient showed significant clinical improvement within three days of initiating appropriate therapy. In conclusion, this case underscores the peril of diagnostic anchoring in severe malaria. Clinical severity must supersede laboratory findings that are incongruent with the patient's condition. The presence of a Plasmodium species other than falciparum on an initial smear does not rule it out as the cause of a severe syndrome. Discordant results between microscopy and RDTs are a critical red flag for mixed infections and mandate immediate, expert parasitological re-evaluation to ensure timely, life-saving treatment.